O programa de formação político-sindical e educacional da App-Sindicato (2007-2014) e a renovação de quadro de dirigentes - Fernandes, Donizete Aparecido (2016)
This work investigates the Program of Political-Syndical and Educational Formation destined to the affiliates of the APP-Union between 2007 and 2014. The program was born in a historical context marked by the ascension of Workers' Party to power, which created a paradox to the syndicalism historically combative, represented by the CUT, which began to engage in the realization of government objectives. The general object of the research is to analyze the proposal for renewal of the APPunion leaders as proposed by the Training Program from 2007 to 2014. We defend the thesis that prevails in the composition of leaders‟ group of APP-Union the balance of power existing between trends and political groups also exist in the CUT and the PT in a very bureaucratic structure, so that the goal of training new composition of leaders is not done according to the proposed objectives. The specific objectives are defined as follows: contextualizing the union question as having references articles of the Marxist Criticism magazine and the Marxist classics; analyze the syndicale movement in Brazil on 1980 – 1990 decades and early twentyfirst century; demonstrate that the books of Political and Trade Union Training and Educational do not reach the objectives proposed, cause its eclecticism and lack of a specific theoretical orientation, and does not alter the direction composition of APP, which continue to be provided by trends or internal groups of APP -Sindicato, a fact that attach to internal union organization. At the end of the research we conclude that at least until now, the desired renewal for the courses is still not making effective. As the main problem, it can be said that training texts, which are taken from various authors are fragmented and decontextualized and, as serious as this, have conflicting theories as to each other, and follow the thematic structure of academic history books. Although the proposed training crave the formation of critical thinking, the choice of texts and general guidelines are fragmentary and disjointed, so that does not meet the objectives.